Influence of Financial Management Competencies on Small Medium Enterprise Creation in Awka South Local Government Area - Samuel Ogbara; Chinedu Chukwunwa (Sean Institute, 2025)
This paper examined the influence of financial management competencies on small medium enterprise creation in Awka South Local Government Area. The paper used descriptive research design with population of 1453 of owners and employees in SMEs in Anambra State. The study adopted Taro Yamane’s formula to determine a sample size of 314. Direct method of data collection was in data collection. Chi-square analysis was used to test the hypothesis of the study at 5% level of significant. The study showed that financial management help SMEs to develop the ability to determine profit of a particular period, prepare sales, cash and production budget, and keep accurate financial records. The study recommended that entrepreneurs should endeavour to go for financial management as this help them to develop the ability to determine profit of a particular period.